Obesidade em felinos - Gentini, Thaís Moreira (Universidade Estadual Paulista (Unesp), 2022)
Feline obesity is a multifactorial disease, and is present all over the globe, to diagnose it, one must use of zoometric measures, palpation and comparison between feline body conformations available in previously validated charts, the nine points one, being considerate the most accurate. For the treatment of the obese cat, a quantity of food is established according to equations that calculate the daily energetic needs for each individual creature. Also, allied with the diet, its interesting to promote a rise in the feline’s physical activity, in order to increase its energy expenditures, which can be done through environmental enrichment. The prevention of obesity itself is always the best alternative, as it promotes health and well-being for the cat and its owners

A obesidade em felinos é uma doença multifatorial e presente no mundo todo, para diagnosticá-la é preciso realizar medidas zoométricas, palpação e comparação da conformação corporal dos felinos com escalas previamente validadas, a considerada mais adequada é a de nove pontos. Para o seu tratamento é estabelecida uma quantidade de alimento a ser fornecido diariamente, de acordo com equações que calculam a necessidade energética diária daquele animal. Aliado a dieta é interessante promover um aumento da atividade física do gato, a fim de aumentar o nível de energia gasto por ele, isso pode ser realizado com enriquecimento ambiental. A prevenção da obesidade é a melhor escolha, pois promove saúde e bem-estar aos gatos e seus tutores.
Feline obesity
Keywords: Obesity; Weight management; Domestic felines; Animal nutrition; Obesidade; Manejo do peso; Felinos domésticos; Nutrição animal